Potential lipase inhibitor for obesity treatment - Alias, Norsyuhada; Leow, Thean Chor; Mohammad Ali, Mohd Shukuri; Salleh, Abu Bakar; Ahmad Tajudin, Asilah; Raja Abd.Rahman, Raja Noor Zaliha (2015)
Pancreatic lipase inhibitors from natural resources are a potential tool for the treatment of obesity. The inhibitory activity of 24 crude extracts of selected Malaysian plants against porcine pancreatic lipase (PPL) was successfully screened, in vitro. Orthosiphon stamineus, Phyllanthus niruri, Murraya paniculata and Averrhoa bilimbi leaves extracts showed more than 70% inhibitions when incubated with PPL at a final concentration of 500 µg/mL for 15 minutes at 37⁰C. P. niruri crude extract exhibited strongest lipase inhibitory activity, with an IC50 value of 27. 65 µg/mL followed by O. stamineus, M. paniculata and A. bilimbi with IC50 values of 34.74, 41.45 and 55.18 µg/mL, respectively. The inhibition mode study disclosed that P. niruri could act as noncompetitive inhibitor. Antioxidant activity of P. niruri extract was measured by 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. P. niruri showed high antioxidant activity with an EC50 value of 7.471 µg/mL. The results suggested that P. niruri has shown potential as a source of natural antilipase and antioxidant.